The effects of time and temperature on umbilical cord gas analysis. (17th November 2022) - Fan, Isabella; Hiersch, Liran; Belov, Yekaterina; Amikam, Uri; Tzur, Yossi; Hershkovitz, Gal; Sindel, Ofra; Alpern, Sharon; Segal, Roy; Dangot, Ayelet; Many, Ariel; Yogev, Yariv; et al.
Abstract: Objective: Our objective was to evaluate the effects of time and temperature on umbilical-cord blood analysis. Methods: This prospective study included the term spontaneous vaginal deliveries. One venous and seven arterial samples were drawn from each umbilical cord within 5 min from delivery. Three samples were immediately refrigerated (3 °C), while all other samples were stored at room temperature (23–26 °C). Samples were analyzed in pairs (refrigerated and room-temperature samples) at 0, 20, 40, and 60 min after delivery for pH and lactate levels. Repeated-measures analysis using a generalized linear model was used to compare the change in pH and lactate values over time. Results: 518 samples from 74 women were analyzed. The mean gestational age was 39.1 ± 1.1 weeks. All neonates had an Apgar score of ≥9 in the 1st and 5th minutes. Mean arterial pH and lactate levels at delivery (time 0) were 7.32 ± 0.07 and 4.00 ± 1.36 mmol/L, respectively. Over time, a statistically significant decrease in pH and a reciprocal increase in lactate levels were observed. The mean change in arterial pH following 60 min was 0.021 ± 0.028 (room-temperature) and 0.016 ± 0.023 (refrigerated); p < 0.001. Compared to pH, a greater change was demonstrated in lactate levels over time; the mean change in lactate following 60 min was −0.896 ± 0.535 (room temperature) and −0.512 ± 0.450 mmol/L (refrigerated). Temperature significantly altered both pH and lactate levels, but lactate levels were altered at earlier time points. Conclusion: Both time and temperature have significant effects on cord blood analysis. Yet, these changes are minor and may not have any clinical significance unless in extreme cases in which medicolegal aspects emerge.